Implementation of targeted next-generation sequencing for the diagnosis of drug-resistant tuberculosis in low-resource settings: a programmatic model, challenges, and initial outcomes - de Araujo, Leonardo; Cabibbe, Andrea Maurizio; Mhuulu, Lusia; Ruswa, Nunurai; Dreyer, Viola; Diergaardt, Azaria; Günther, Gunar; Claassens, Mareli; Gerlach, Christiane; Utpatel, Christian; Cirillo, Daniela Maria; Nepolo, Emmanuel; et al. (Frontiers in Public Health, 2023)
Targeted next-generation sequencing (tNGS) from clinical specimens has the potential to become a comprehensive tool for routine drug-resistance (DR) prediction of Mycobacterium tuberculosis complex strains (MTBC), the causative agent of tuberculosis (TB). However, TB mainly affects low-and middle-income countries, in which the implementation of new technologies have specific needs and challenges. We propose a model for programmatic implementation of tNGS in settings with no or low previous sequencing capacity/experience.We highlight the major challenges and considerations for a successful implementation. This model has been applied to build NGS capacity in Namibia, an upper middle-income country located in Southern Africa and suffering from a high-burden of TB and TB-HIV, and we describe herein the outcomes of this process.